Social protection and revenue collection: How they can jointly contribute to strengthening social cohesion - Francesco Burchi; Armin von Schiller; Christoph Strupat (International Social Security Review, 2020)
Social protection and revenue collection are often regarded as potential drivers of social cohesion. The article joins this debate, providing three main contributions. First, we carefully discuss the concept of social cohesion and endorse one specific definition. Second, we propose using the concept of the “fiscal contract” as the key theoretical lens to understand the often neglected potential joint effects of social protection and revenue collection policies on social cohesion. Third, we illustrate three main mechanisms through which these policies can have positive or negative impacts on the different components of social cohesion and highlight the relevance of these for policy-makers deliberations.
Keywords: 300; social cohesion; social protection; collection of contributions; fiscal policy; public finance; taxation; international; cohésion sociale; protection sociale; recouvrement des cotisations; politique fiscale; finances publiques; fiscalité; international; cohesión social; protección social; recaudación de cotizaciones; política fiscal; finanzas públicas; tributación; internacional; sozialer Zusammenhalt; Sozialschutz; Beitragseinzug; Fiskalpolitik; öffentliche Finanzen; Besteuerung; international